Group and Individual-level Change on Health-related Quality of Life in Chiropractic Patients with Chronic Low Back or Neck Pain - Hays, Ron D. (Spine (Phila Pa 1976), 2019)
STUDY DESIGN: Prospective observational study. OBJECTIVE: To evaluate group-level and individual-level change in health-related quality of life among persons with chronic low back pain or neck pain receiving chiropractic care in the United States. SUMMARY OF BACKGROUND DATA: Chiropractors treat chronic low back and neck pain, but there is limited evidence of the effectiveness of their treatment METHODS: A 3-month longitudinal study of 2,024 patients with chronic low back pain or neck pain receiving care from 125 chiropractic clinics at 6 locations throughout the United States was conducted. Ninety-one percent of the sample completed the baseline and 3-month follow-up survey (n = 1,835). Average age was 49, 74% females, and most of the sample had a college degree, were non-Hispanic White, worked full-time, and had an annual income of $60,000 or more. Group-level (within group t-tests) and individual-level (coefficient of repeatability) changes on the Patient-Reported Outcomes Measurement Information System (PROMIS(®)) v2.0 profile measure was evaluated: 6 multi-item scales (physical functioning, pain, fatigue, sleep disturbance, social health, emotional distress) and physical and mental health summary scores. RESULTS: Within group t-tests indicated significant group-level change (p < 0.05) for all scores except for emotional distress, and these changes represented small improvements in health (absolute value of effect sizes ranged from 0.08 for physical functioning to 0.20 for pain). From 13% (physical functioning) to 30% (PROMIS-29 Mental Health Summary Score) got better from baseline to 3 months later according to the coefficient of repeatability. CONCLUSIONS: Chiropractic care was associated with significant group-level improvement in health-related quality of life over time, especially in pain. But only a minority of the individuals in the sample got significantly better (“responders”). This study suggests some benefits of chiropractic on functioning and well-being of patients with low back pain or neck pain.